Psychometric properties of Persian version of Midwives' Attitudes and Beliefs Questionnaire toward physiological childbirth - Narges Sadeghzadeh; Leila i Amiri-Farahan; Mohammad Asghari Jafarabadi (Mashhad University of Medical Sciences, 2020)
Introduction: Since attitudes and beliefs can predict behavior, policy, and performance of an individual, so the midwives' attitudes and beliefs toward labor and delivery can also affect their caring behavior and performance, and the prenatal consequences of the mother and neonate. And the baby is effective. There was no suitable Persian tool to measure the attitude and belief of midwives toward physiological delivery, so this present study was performed with aim of translating and psychometric evaluation of the Persian version of the questionnaire of attitude and belief of midwives toward physiological delivery. Methods: This methodological study was performed on 200 midwives working in the selected hospitals of Tehran University of Medical Sciences in 2018. The midwives were asked to complete a demographic questionnaire and midwives' attitudes and beliefs questionnaire toward physiological childbirth. At first, the face and content validity of the questionnaire was performed qualitatively. Then, construct validity was performed by confirmatory factor analysis. The reliability of the questionnaire was confirmed by stability reliability method and internal consistency. Results: The face validity and qualitative content of the questionnaire of midwives' attitudes and beliefs toward physiological childbirth were confirmed. Also, confirmatory factor analysis by estimating weight Partial Least Squares showed that the Persian version of this questionnaire has a suitable structure. In order to determine the reliability, the Cronbach's alpha coefficient was estimated as 0.68 to 0.733 for domains of the tools and the Intra-class correlation coefficient was 0.78; both of which indicated good reliability of the Persian version of the questionnaire. Conclusion: Persian version of the questionnaire of midwives' attitude and belief toward physiological childbirth is valid and reliable and can be used as an appropriate instrument for assessing the attitude and belief of midwives toward physiological childbirth in Iran.